Enantioselective Total Synthesis and Absolute Configuration Assignment of (+)‐Tronocarpine Enabled by an Asymmetric Michael/Aldol Reaction. (3rd February 2020) - Tan, Dong‐Xing; Zhou, Jie; Liu, Chao‐You; Han, Fu‐She
Abstract: We present the first asymmetric total synthesis and absolute configuration determination of (+)‐tronocarpine. The [6.5.7.6.6] pentacyclic core was constructed at an early stage by using a sequential cyclization strategy through a newly developed catalytic asymmetric Michael/aldol cascade to build the aza[3.3.1]‐bridged cycle and a tandem reduction/hemiamidation procedure to assemble the seven‐membered lactam. The side‐chain functionalities were incorporated at a late stage by several appropriately orchestrated manipulations under mild conditions. The synthesis of enantiomerically pure (+)‐tronocarpine was achieved through a 20‐step longest linear sequence from tryptamine. Abstract : Der pentacyclische Kern von Tronocarpin wurde in einem frühen Synthesestadium aufgebaut. Zielführend waren eine neue katalytische asymmetrische Michael/Aldol‐Kaskade zur Bildung des Aza‐verbrückten Ringsystems und eine Tandemreaktion aus Reduktion und Halbamidierung zum Aufbau des 7‐gliedrigen Lactams. Weitere Funktionalitäten wurden später unter milden Bedingungen eingeführt.